(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Per una nozione di movimento ecclesiale. Le indicazioni di Giovanni Paolo II rivisitate nel 2016 dalla lettera “Iuvenescit Ecclesia” della Congregazione per la dottrina della fede - 2. Gli orientamenti di papa Francesco nei confronti dei movimenti ecclesiali. Le fonti - 3. Custodire il carisma - 4. Il rischio della autoreferenzialità - 5. Altre possibili deviazioni - 6. Le preoccupazioni di papa Francesco - 7. La missione dei movimenti ecclesiali - 8. Avvertenze conclusive. «You can be the arms, hands, feet, mind and heart of a Church “which goes forth”». Pope Francis and the ecclesial movements ABSTRACT: Pope Francis believes that ecclesial movements are a gift of the Spirit for those who participate in them and for the whole Church. But, unlike its immediate predecessors, he deals intensively, in language that is at times severe, with the dangers they may run into. In this regard, however, it should be noted that similar warnings are also made with regard to other ecclesial realities. In any case, it cannot be denied that the current Pontiff looks favourably on the movements, since he entrusts them with very important and demanding tasks in the fulfillment of the Church’s mission.